Electrodeposition of rhenium from chloride melts: Electrochemical nature, structure and applied aspects - Vinogradov-Zhabrov O.N.; Minchenko L.M.; Esina N.O.; Pankratov A.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Processes involved in the electrodeposition of rhenium from chloride melts have been studied over the temperature interval from 680 to 970 0C at a cathodic current density of 5 to 250 mA/cm2. It has been found that rhenium is deposited in the form of continuous layers. In addition to that the growth of deposits as separate single-crystal needles has also been noticed. Continuous layers had axial growth textures. The crystallographic direction of the textures is due to electrolysis conditions, such as concentration of oxygen-containing impurities, temperature, melt composition and cathodic current density. When the concentration of oxygen-containing impurities in the melt decreased, electrolysis temperature increased, the average radius of the supporting electrolyte cations became smaller, or cathodic current density diminished, the direction of the growth textures was changing as follows: (1010) →(1120) →(101L) →(0001) →(0001)needles. The microhardness of the deposits in this series is 900 to 250 kg/mm2. The growth of deposits on textured rhenium substrates and single crystals having different orientations, including bent substrates, was studied. It has been found that the epitaxial growth is virtually unlimited in depth if the orientation of the substrate coincides with the growth texture under given conditions. If the substrate orientation deviated from the growth texture, the epitaxial growth was nearly absent. Kinetic parameters were measured using the galvanostatic method. The exchange current density was determined over the interval of (0.01-0.1) A/cm2 depending on the concentration of oxygen-containing impurities, cation composition, type of the surface and its condition. The parameter α⋅Z, which was estimated by two methods, was equal to 2.1-3.1. The diffusion coefficient of rhenium ions has been found to be 2.8 ⋅10 −5 cm2/s at 790 0C and 3.5 ⋅10 −5 cm2/s at 840 0C. Galvanoplastic production of rhenium products, such as crucibles, ampoules foils, wire, and intricate articles, was performed.